G544(P) What do young people think can be improved with the transition to adult services?. (25th October 2020) - Farr, E; Alam, SMA; Thomas, S; Van der Voort, JH
Abstract : Aims: Local audit showed NICE Guidance regarding the transition of young people (YP) to adult services is not well implemented. This qualitative service improvement project investigated the perspectives of YP transitioning from a tertiary paediatric nephrology service to adult services. The aim was to identify key factors underpinning positive and negative experiences of transition and provide suggestions for change in practice to better support transition for YP. Methods: Institutional ethics approval was sought but deemed unnecessary and informed written consent gained. Young people attending a renal patient summer camp were questioned through critical incident technique via both written questionnaire and semi-structured focus group discussion overseen by two researchers. Transcribed responses were thematically analysed by two investigators independently, then agreed upon jointly. Results: Of 11 participants (13–30 y, average 21 y, 36% female), only 30% knew what ReadySteadyGo was, the locally employed transition tool. 15 themes were identified, organised into 5 key factors underpinning positive experiences of transition: 1) Preparation for adult services; 2) Approach adopted by staff; 3) Chances to talk; 4) Peer support; and 5) Environmental improvement. Conclusion: Young people generated recommendations to improve the experience of transition. These included improving preparation through familiarisation with staff and places by being introduced to the new team sooner with more opportunities to interact, trips to the new unit and more information about the practicalities within adult services. YP wanted staff to be more like friends, ideally with some familiar faces on both sides of transition. They wanted staff to ease YP into transition gradually and tailor the process to each YP's individual needs, to be honest about pros and cons and provide truthful experiences from other patients, acknowledge YP's concerns by listening to how they feel and empower YP to take more involvement with learning to promote self-efficacy. Additionally, YP wanted the opportunity to talk about their life experiences, and particularly valued the support of peers. Through socialising with others their age with similar chronic conditions, YP were able to share experiences and feel normal. Finally, YP wanted adult services to invest in comfort and entertainment as provided in paediatric services.